Pengaruh Strategi Marketing Mix Terhadap Keputusan Pembelian pada Alyasini Mart Rembang - Mukhammad Shodiqin; Nuriyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In keeping up with the development of the lifestyle of the surrounding residents. As well as business strategy movements such as minimarkets such as Indomart and Alfamart that are familiar everywhere, performance efforts to retain Alyasini Mart minimarket consumers are very important in order to plan the overall marketing communication program process or marketing mix. This study aims to explain the influence of marketing mix strategy on purchasing decisions at Alyasini Mart Rembang, and among the variables are products, prices, promotions, locations. To measure the above influence, the researcher used a quantitative approach with a sample survey type, this study was 100 respondents who were consumers of Alyasini Mart. The data analysis used is analysis with multiple regression analysis, validity test of classical assumption test, hypothesis test (T and F test) with the help of spss, the results of this study show that product variables partially have a positive and significant effect on purchase decisions. Price partially has a positive and significant impact on purchase decisions. Promotions partially have a positive and significant impact on purchase decisions. Places partially have a positive and significant influence impact on purchase decisions. Marketing Mix (Product, Price, Promotion, Place) simultaneously has a positive and significant influence on purchasing decisions at Alyasini Mart Rembang.